2017
DOI: 10.4317/jced.52953
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of 14 cases of odontogenic myxoma and review of the literature

Abstract: BackgroundOdontogenic myxoma is a rare benign neoplasm that originates from odontogenic ectomesenchyme. There is no standard of care and recurrences are frequent after conservative surgical procedures.Material and MethodsA retrospective study conducted at a single cancer center, with analysis of medical records of all patients diagnosed with odontogenic myxoma from 1980 to 2010, along with a literature review.ResultsThere were 14 patients with diagnosis of odontogenic myxoma (OM). Most patients were female (78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 14 publications
2
33
0
10
Order By: Relevance
“…In mandible, the simultaneous involvement of the anterior and posterior region occurred in 4.1% and in the maxilla in 2.98%. Some studies have not clearly demonstrated the OM localization 3,14,15,20,21,25,27,28,31,35‐38,45,48,50,52,53,57,60 . Previously to the treatments, 93.69% of OM was diagnosed by biopsy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In mandible, the simultaneous involvement of the anterior and posterior region occurred in 4.1% and in the maxilla in 2.98%. Some studies have not clearly demonstrated the OM localization 3,14,15,20,21,25,27,28,31,35‐38,45,48,50,52,53,57,60 . Previously to the treatments, 93.69% of OM was diagnosed by biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis should involve a clinical, radiographic and microscopic features 5 . Surgical procedures are the best treatment modality for OM and involved curettage until total resection of bone affected 3,7,30 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations